Engineered endolysin-based "artilysins" to combat multidrug-resistant gram-negative pathogens - Briers, Yves; Walmagh, Maarten; Van Puyenbroeck, Victor; Cornelissen, Anneleen; Cenens, William; Aertsen, Abram; Oliveira, Hugo; Azeredo, Joana; Verween, Gunther; Pirnay, Jean-Paul; Miller, Stefan; Volckaert, Guido; et al. (mBio, 2014)
The global threat to public health posed by emerging multidrug-resistant bacteria in the past few years necessitates the development of novel approaches to combat bacterial infections. Endolysins encoded by bacterial viruses (or phages) represent one promising avenue of investigation. These enzyme-based antibacterials efficiently kill Gram-positive bacteria upon contact by specific cell wall hydrolysis. However, a major hurdle in their exploitation as antibacterials against Gram-negative pathogens is the impermeable lipopolysaccharide layer surrounding their cell wall. Therefore, we developed and optimized an approach to engineer these enzymes as outer membrane-penetrating endolysins (Artilysins), rendering them highly bactericidal against Gram-negative pathogens, including Pseudomonas aeruginosa and Acinetobacter baumannii. Artilysins combining a polycationic nonapeptide and a modular endolysin are able to kill these (multidrug-resistant) strains in vitro with a 4 to 5 log reduction within 30 min. We show that the activity of Artilysins can be further enhanced by the presence of a linker of increasing length between the peptide and endolysin or by a combination of both polycationic and hydrophobic/amphipathic peptides. Time-lapse microscopy confirmed the mode of action of polycationic Artilysins, showing that they pass the outer membrane to degrade the peptidoglycan with subsequent cell lysis. Artilysins are effective in vitro (human keratinocytes) and in vivo (Caenorhabditis elegans). M.W. held a predoctoral fellowship of the "Instituut voor aanmoediging van Innovatie door Wetenschap en Technologie in Vlaanderen" (IWT Flanders). Y.B. and M. W. were supported by IWT Flanders and Y.B. by a postdoctoral fellowship of the "Bijzonder Onderzoeksfonds-KU Leuven." S. M. is an employee of Lisando GmbH. R. L. acts as scientific adviser to Lisando GmbH.